Hemocoagulase reduces postoperative bleeding and blood transfusion in cardiac surgical patients: A PRISMA-compliant systematic review and meta-analysis - Yao, Yun-Tai (Medicine (Baltimore), 2019)
BACKGROUND: Hemocoagulase is isolated and purified from snake venoms. Hemocoagulase agents have been widely used in the prevention and treatment of surgical bleeding. A systematic review was performed to evaluate the effects of hemocoagulase on postoperative bleeding and transfusion in patients who underwent cardiac surgery. METHODS: Electronic databases were searched to identify all clinical trials comparing hemocoagulase with placebo/blank on postoperative bleeding and transfusion in patients undergoing cardiac surgery. Two authors independently extracted perioperative data and outcome data. For continuous variables, treatment effects were calculated as weighted mean difference and 95% confidential interval (CI). For dichotomous data, treatment effects were calculated as odds ratio and 95% CI. Each outcome was tested for heterogeneity, and randomized-effects or fixed-effects model was used in the presence or absence of significant heterogeneity. Sensitivity analyses were done by examining the influence of statistical model and individual trial on estimated treatment effects. Publication bias was explored through visual inspection of funnel plots of the outcomes. Statistical significance was defined as P < .05. RESULTS: Our search yielded 12 studies including 900 patients, and 510 patients were allocated into hemocoagulase group and 390 into control group. Meta-analysis suggested that, hemocoagulase-treated patients had less bleeding volume, reduced red blood cells and fresh frozen plasma transfusion, and higher hemoglobin level than those of controlled patients postoperatively. Meta-analysis also showed that, hemocoagulase did not influence intraoperative heparin or protamine dosages and postoperative platelet counts. Meta-analysis demonstrated that, hemocoagulase-treated patients had significantly shorter postoperative prothrombin time, activated partial thromboplastin time, and thrombin time, higher fibrinogen level and similar D-dimer level when compared to control patients. CONCLUSION: This meta-analysis has found some evidence showing that hemocoagulase reduces postoperative bleeding, and blood transfusion requirement in patients undergoing cardiac surgery. However, these findings should be interpreted rigorously. Further well-conducted trials are required to assess the blood-saving effects and mechanisms of Hemocoagulase.